2018
DOI: 10.1111/jam.14124
|View full text |Cite
|
Sign up to set email alerts
|

Grape berry surface bacterial microbiome: impact from the varieties and clones in the same vineyard from central China

Abstract: Aims: Bacterial microbiome on grape berry surface may play an important role in grape quality and health. This study aims to investigate the impact of grape varieties and clones on grape berry surface bacterial microbiome from the same vineyard. Methods and Results: High-throughput sequencing strategy was used to investigate the bacterial diversity and abundance on the grape surfaces of 12 clones belonging to six varieties grown in the same vineyard of Zhengzhou Fruit Research Institute in Henan Province. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…Grape varieties and clones exert marked impact on grape surface bacteria within vineyard. For example, Bacteroidetes , Chloroflexi , Acidobacteria , and Planctomycetes are clone- specific phyla alongside the prevalent phylum Cyanobacteria , Proteobacteria , and Firmicutes (Zhang et al, 2019). This is in contrast with findings by Bokulich et al (2014) who showed that the cultivar-specific influence on microbial diversity is weak in larger scales.…”
Section: Microbial Biogeography: a Microbial Insight To Understand Vamentioning
confidence: 99%
“…Grape varieties and clones exert marked impact on grape surface bacteria within vineyard. For example, Bacteroidetes , Chloroflexi , Acidobacteria , and Planctomycetes are clone- specific phyla alongside the prevalent phylum Cyanobacteria , Proteobacteria , and Firmicutes (Zhang et al, 2019). This is in contrast with findings by Bokulich et al (2014) who showed that the cultivar-specific influence on microbial diversity is weak in larger scales.…”
Section: Microbial Biogeography: a Microbial Insight To Understand Vamentioning
confidence: 99%
“…The grape surface is colonized by different microorganisms, mainly filamentous fungi, bacteria and yeasts, which in relation to the final product may have positive or negative effects (Milanović et al, 2013;Alessandria et al, 2015). Several environmental factors, such as geographical location, climatic conditions (temperature, rainfall, wind) and vineyard treatments, affect the microbial communities present on the grape surface at harvest (Barata et al, 2012;Bokulich et al, 2014;Zhang et al, 2019). Many of those factors may also interact, impacting on the microbial diversity and, consequently, wine quality (Barata et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several environmental factors such as geographical region, climatic condition (temperature, humidity, UV radiation, etc. ), availability of nutrients and farming treatments could influence the composition of microbiota [4,5,6,7,8,9]. The possible interactions among the factors could also affect biodiversity and stability of microbiota, grapevine health and as final consequence, the quality of wines [1,10].…”
Section: Introductionmentioning
confidence: 99%